Slot antenna design for a wirelessly powered implantable microcooler for neuronal applications - Dinis, H. (2017)
Implantable medical devices are becoming smaller by the day, with more efficient electronics and smaller power demands. Nevertheless, there are some applications in which power demands are inherently high, and solutions must be found in order to keep the devices as small as possible. In this paper, we propose an antenna to be used in wirelessly powering a focal brain cooling implant based on a Peltier device. This antenna is designed in order to act as a heatsink for the device with the goal of minimizing its final volume, therefore design constrains such as size limitations and geometry restrictions are considered.